(untitled) (International Journal of Engineering and Computer Science, 2015)
Learning Management System (LMS) is a software application for administration, delivering, tracking and reporting on elearning (electronic learning) courses to various organizations, educational institutes, and online websites. LMS launches e-learning courseware and deliver it with flexibility. LMS balances between functionality and ease of use. LMS provides the user with simple and modern user interface. Most organization uses different LMS for launching new training courseware to their employee from a central server and it is easy to track the employee understanding of the course at the end of the training by an online assessments. LMS uses AICC and SCORM standards for tracking the e-learning courses. The standards depend on the development of the course ware. In this paper, the detailed survey about the AICC and SCORM used in LMS are discussed.